2023
DOI: 10.1055/a-1974-9078
|View full text |Cite
|
Sign up to set email alerts
|

Transethosomes: A Promising Challenge for Topical Delivery Short Title: Transethosomes for Topical Delivery

Abstract: Skin provides an excellent barrier to molecular transport, as the stratum corneum is the most formidable barrier to the passage of most pharmaceuticals. Various attempts have been made to improve drug administration into the body through intact skin. Though very few routes are as attractive as the topical route, drug transport through the skin is challenging. To overcome the challenges, researchers have found a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 101 publications
(126 reference statements)
0
3
0
Order By: Relevance
“…Ensuring reproducibility and cost‐effectiveness is crucial to facilitate their widespread use in pharmaceutical applications. Developing robust manufacturing processes that maintain the integrity and quality of TEs at larger scales is essential 110 . Efficient mixing, temperature control, and homogenization techniques are crucial to ensure the reproducibility and uniformity of TE vesicles.…”
Section: Challenges and Strategies To Overcomementioning
confidence: 99%
See 1 more Smart Citation
“…Ensuring reproducibility and cost‐effectiveness is crucial to facilitate their widespread use in pharmaceutical applications. Developing robust manufacturing processes that maintain the integrity and quality of TEs at larger scales is essential 110 . Efficient mixing, temperature control, and homogenization techniques are crucial to ensure the reproducibility and uniformity of TE vesicles.…”
Section: Challenges and Strategies To Overcomementioning
confidence: 99%
“…Developing robust manufacturing processes that maintain the integrity and quality of TEs at larger scales is essential. 110 Efficient mixing, temperature control, and homogenization techniques are crucial to ensure the reproducibility and uniformity of TE vesicles. Optimization of TE manufacturing processes through process analytical techniques (PAT) and automation can improve scalability, reduce production costs, and enhance reproducibility.…”
Section: Challenges and Strategies To Overcomementioning
confidence: 99%
“…In another investigation, investigators Lang et al [34] assessed the effectiveness of paclitaxel-loaded topical nanoparticles for treating cutaneous metastases from nonmelanoma cancer. Several reports have shown that nanodrug delivery systems such as liposomes, cubesomes, transferosomes, ethosomas, niosomes, spongosomes, etc., are used for the topical administration of drugs through intracellular, transapendagic, and transcellular routes [25,32,35,36]. Nanotechnology methods provide an opportunity to improve the treatment of many forms of cancer including skin cancer.…”
Section: Introductionmentioning
confidence: 99%